Efektivitas Program Sistem Informasi Kesejahteraan Sosial (SIKS-Ng) dalam Mendukung Program SLRT dan Puskesos Dinas Sosial Provinsi Sulawesi Selatan - Andi Muhammad Asrandi T; Sari Apriliya Wati; Abdul Wahab; Alfian Alfian (Jurnal Indonesia Sosial Sains, 2022)
Poverty in South Sulawesi Province has experienced a significant decline with a rate of 1.01% from 2016 to 2018, where this decline is in line with the implementation of an Integrated Social Protection System called "Integrated System of Referral Services (SLRT) and Social Welfare Centers (Puskesos). Through this system, the South Sulawesi Provincial Government seeks to provide integrated social protection to the community by improving the quality of life of the poor. This article aims to explain integrated social protection for the poor in South Sulawesi Province through SLRT and Puskesos. This research uses a qualitative method used to describe the process of organizing integrated social protection. The results show that social protection efforts for the poor through an integrated social protection system are implemented by applying five aspects of services, such as one stop service, partnerships, service mechanism programs, case management, and information and intervention systems.